Peranan Gereja Batak Karo Protestan dalam Melestarikan dan Mempertahankan Kebudayaan Suku Batak Karo - Yolanda Rafella M. Sari; Payerli Pasaribu (Universitas Negeri Medan, 2019)
This study aims to determine the mission of the Protestant Karo Batak Church which is directly related to cultural preservation, knowing the causes of Karo people who are congregations of GBKP in Medan Selayang District are better able to maintain their culture than those who are not GBKP congregations and activities and efforts made by the Karo Batak Church Protestant in preserving and maintaining the Karo Batak culture. To obtain the necessary data, the researcher uses field research methods with a qualitative descriptive approach. Then the collecting technique is done by observing the research location, namely GBKP in Medan Selayang District. The results of this study indicate that the GBKP has a mission that is directly related to cultural preservation. This mission is an effort made to realize the GBKP's vision, which is